2014
DOI: 10.5213/inj.2014.18.3.145
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between the Treatment Efficacy and the Sympathetic Activity in Men With Lower Urinary Tract Symptoms

Abstract: PurposeIn this study, we examined the difference in the treatment efficacy depending on the sympathetic activity in men with lower urinary tract symptoms (LUTS).MethodsIn the current single-center, retrospective study, we evaluated a total of 66 male patients aged 40-70 years of age, presenting with LUTS, whose International Prostate Symptom Score (IPSS) exceeded 8 points. They had a past 3-month history of taking alfuzosin XL, and their heart rate variability (HRV) was measured before and after the treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Sympathetic activity was not directly measured in this study, but our findings were compatible with those of other studies that measured sympathetic activity and suggested that sympathetic activity could be triggered via storage symptoms. 4,20,21,28 When the cutoff value was set at 40 g, we observed that the We did not find any relationship between postvoiding residual volume and SBP. This may be explained by the low residual urine volumes.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Sympathetic activity was not directly measured in this study, but our findings were compatible with those of other studies that measured sympathetic activity and suggested that sympathetic activity could be triggered via storage symptoms. 4,20,21,28 When the cutoff value was set at 40 g, we observed that the We did not find any relationship between postvoiding residual volume and SBP. This may be explained by the low residual urine volumes.…”
Section: Discussionmentioning
confidence: 61%
“…22 According to Jang et al, in patients with sympathetic hyperactivity, alpha blockers were less effective. 28 They commented that sympathetic hyperactivity was a negative prognostic factor for progression of benign prostate enlargement. However, this correlation was only observed in relation to the total International Prostate Symptom Score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Other possible mechanisms include access to and utilization of health care, [4][5][6]8 as well as physiological stress responses to the experience of adverse SDoH and unmet social needs, particularly when those experiences are chronic or recurrent in nature. 9,10 These mechanisms may explain the association between food insecurity and LUTS if food insecurity is a proxy for the broader experience of social inequities. Basic science is important because findings can inform prevention strategies and treatments that target the mechanisms thought to be most influential in the development or maintenance of LUTS.…”
mentioning
confidence: 99%